PEMANFAATAN CHATBOT MENGGUNAKAN NATURAL LANGUAGE PROCESSING UNTUK PEMBELAJARAN DASAR-DASAR GUI TKINTER PADA BAHASA PEMROGRAMAN PYTHON - Sindy Nova; Nurul Khotimah; Maria Y Aryati Wahyuningrum (Jurnal Ilmiah Teknik, 2024)
Along with the significant development of technology today, websites have become an alternative media as a means of promotion and information dissemination. The website has many facilities that can make things easier for users, one of which is a chatbot. Chatbots or what are commonly known as virtual assistants are able to understand and respond to user requests with the right answers. The use of the Python programming language is quite popular among novice programmers, its simple syntax and clear and logical code means that this language is often used for creating games, websites, prototyping and also for handling big data. One of the modules for creating Graphical User Interface (GUI) applications in Python is Tkinter. In this research, a chatbot will be created which aims to make it easier for users to find solutions to the problems they face when using the Python programming language in the Tkinter GUI module using Natural Language Processing in an interactive way.